2013
DOI: 10.1111/ans.12362
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Indigenous Surgical Workforce for Australasia

Abstract: Background: Progress has been made in Australia and New Zealand to increase the numbers of indigenous students (Aboriginal, Torres Strait Islander and Maori) entering primary medical qualification courses. In New Zealand, up to 20 Maori are graduating annually, with similar numbers possible in Australia, creating a potential opportunity to develop an indigenous surgical workforce. Methods: A literature review identified factors utilized by medical schools to attract indigenous students into medical careers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Indigenous and non-Indigenous academics have named mentorship as a potent practice supporting the retention of Indigenous students in higher education in general, [1][2][3][4][5] and in health sciences specifically. [6][7][8][9][10][11][12] With this in mind, there is a strong need to invest in the mentorship of Indigenous health professionals and scholars. Doing so would potentially promote cultural safety, career success for Indigenous health professionals, and culturally appropriate health service and research environments, 10,[13][14][15][16] as current services, practices, and approaches to health and health research are not meeting the needs of Indigenous people.…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous and non-Indigenous academics have named mentorship as a potent practice supporting the retention of Indigenous students in higher education in general, [1][2][3][4][5] and in health sciences specifically. [6][7][8][9][10][11][12] With this in mind, there is a strong need to invest in the mentorship of Indigenous health professionals and scholars. Doing so would potentially promote cultural safety, career success for Indigenous health professionals, and culturally appropriate health service and research environments, 10,[13][14][15][16] as current services, practices, and approaches to health and health research are not meeting the needs of Indigenous people.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Addressing the under-representation of indigenous health professionals is a globally acknowledged step in overcoming health inequities in indigenous populations. [18][19][20] M aori and Pasifika remain underrepresented in the AoNZ health workforce, 18,21 failing to meet the targets outlined in RACS Strategic Plans. [22][23][24] There are numerous barriers to women achieving a career in surgery 25,26 and despite outnumbering men in medical schools, 21 they are significantly under-represented in surgical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting minority group access to health careers has received attention not only in New Zealand but globally (Aramoana et al , 2013; Curtis et al , 2012; Patterson and Carline, 2006; Salto et al , 2014; Terrell, 2006). Patterson and Carline (2006) found that positive relationships between health professionals and students in secondary schools help improve minority students’ career choices.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The pipeline approach to assist with health career selection is noted in the literature (Aramoana et al , 2013; Curtis et al , 2012; Neville et al , 2010; Patterson and Carline, 2006; Salto et al , 2014), however only two primary research studies provided evidence of its effectiveness (Neville et al , 2010, Salto et al , 2014). Neville et al ’s (2010) evaluation of the success of PI revealed that not only did PI provide information for students interested in health careers, but it also sparked enthusiasm and encouraged students to think about career ambitions.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation